2008
DOI: 10.1001/archpedi.162.6.526
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Nodules and Cancer in Children and Adolescents Affected by Autoimmune Thyroiditis

Abstract: The observed prevalences of thyroid nodules and thyroid cancer in our JAT case series were 31.5% and 3.0%, respectively. Papillary carcinoma was the only histotype detected. The finding of lymphadenopathy, a lack of response to levothyroxine therapy, and nodule hypoechogenicity suggested malignancy. Fine-needle aspiration biopsy was reliable in selecting patients for referral to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
6
15

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(141 citation statements)
references
References 31 publications
9
111
6
15
Order By: Relevance
“…To our knowledge, no studies have been carried out in children and adolescent populations regarding the prognostic value of thyroid autoimmunity for the outcome of DTC. On the other hand, some studies report the prevalence of DTC in children with CLT, which was found to be 1.3-3.0% (15,16). In one of those studies (15), more girls were affected by CLT, but males with CLT had an increased risk to develop thyroid cancer (odds ratio (OR), 2.95; 95% confidence interval (CI), 1.44-6.20).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no studies have been carried out in children and adolescent populations regarding the prognostic value of thyroid autoimmunity for the outcome of DTC. On the other hand, some studies report the prevalence of DTC in children with CLT, which was found to be 1.3-3.0% (15,16). In one of those studies (15), more girls were affected by CLT, but males with CLT had an increased risk to develop thyroid cancer (odds ratio (OR), 2.95; 95% confidence interval (CI), 1.44-6.20).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…However, the frequency of PTC in children and adolescents with CLT has been evaluated in two published studies. In the first one, 11 of 365 children and adolescents (3%) with CLT were diagnosed with PTC (15), and in the second study, three of 228 Greek children and adolescents (1.3%) with CLT presented PTC (16).…”
Section: Introductionmentioning
confidence: 98%
“…However, one report shows an increased prevalence of thyroid nodules perhaps as high as 30% with 7 of 11 PTC only detected by US examination (108). It is unclear how many of these would have achieved clinical importance, however.…”
Section: In Children With Dtcmentioning
confidence: 99%
“…Применение высокоразрешающего УЗИ в этой группе пациентов позволяет выявлять не-пальпируемые образования, однако нет убедитель-ных данных в пользу доклинического скрининга этих узлов, поскольку их ранняя диагностика существен- Ограничены данные по частоте РЩЖ на фоне аутоиммунного тиреоидита (АИТ) у детей. В тексте приводится одна ссылка на наблюдательное исследо-вание итальянских авторов [19]. Из 365 детей в возрас-те от 3 до 17 лет с АИТ ТАБ была выполнена в 39 слу-чаях при узлах более 1 см и в 4 -менее 1 см в диаметре, но с подозрительными ультразвуковыми признаками.…”
Section: из обсуждения раздела рекомендаций по узловому зобу у детейunclassified